What People Want : Investigating Inclusive Insurance Demand in Ethiopia - World Bank Group (World Bank, Washington, DC, 2018)
One important barrier to insurance markets that are more inclusive is the necessity to better understand the needs of low-income and other un- and underserved populations. These people are not currently clients of insurers and are difficult for insurers to reach through normal operations. As a result, many well-motivated efforts to provide client solutions can fail because of a misunderstanding or lack of understanding of the client’s situation. This publication explores the situation in Ethiopia where the population has unserved needs that can be met with affordable products they actually want. The results show a clear gap between the effects of various financial shocks and households’ ability to cope with them and a clear gap of unmet but insurable risks. The results also show that experience with and knowledge of insurance is very low, but this can be leveraged as an opportunity. This study, along with applying generally accepted wisdom, could help innovations in microinsurance more likely to succeed.